Physiological and anthropometrical variables of Iranian elite kayakers - Isanezhad, A.; Agha Alinejad, H.; Donyamali, A.; Sohrabain, A.; Tahmasbi, W. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Anthropometric profiles of World-class athletes offer useful data for coaches when initially selecting talented individuals for development programs (Ackland et al., 2003). Sprint kayaking is characterized by exceptional demands on upper body performance (Michael et al., 2008). Olympic kayak paddlers not only need a high aerobic power, but the anaerobic contribution is also very important for successful performance (Bishop 2000). The aim of this study was investigated of physiological and anthropometrical profile of Iranian elite kayakers. Methods: Eight Iranian male kayak athletes with mean age: 19.7±1.98 (year) were examined. Anthropometric measurements: A total of anthropometric variables were directly and indirectly measured according to the methods of standard International Society for the Advancement of Kinanthropometry (ISAK). Aspect of upperbody peak power and anaerobic capacity using the 30-second exhaustive Wingate Anaerobic Test (WAnT). An incremental test was used to determine . Breath-by-breath gas analysis was conducted throughout using an automated Jaeger Oxycon Pro system ( cosmed , Finland). All physiological testing was conducted on a calibrated, wind- braked kayak ergometer (K1 Ergo, Garran, Australia). Descriptive statistics were performed on the group data using standard statistical procedures. (Mean±SD). Result: Anthropometrical and body composition measurements indicated that: age: 19.7±1.98(year) ,straight height: 184.21±5.27(cm), sitting height: 98.43±1.62(cm) ,arm span:189.21± 5.95(cm) ,body mass: 79.04± 4.66(kg) ,lean body mass:71.81±3.59(kg) ,body fat: 10.84±6.18(percent) ,BMI: 21.69± 4.7(kg/m2). Aerobic and anaerobic tests showed: Vo2max: 4.07±0.24 (L/min), Vo2max: 50.69±3.34 (ml/kg/min) ,Heart rate to Vo2max: 183.1± 7.4(b/min) ,Mean power:395.45±23.46(W) ,Mean power: 4.5± 0.24(W/kg) ,Peak power: 882.54±120.36 ,Peak power: 11.00± 1.27. Discussion: Our result indicated that these kayakers have straight and siting height near the average of world elite kayakers (Ackland et al 2003). Their relative VO2 max was 50.69±3.34 (ml/kg/min) and its accordance with Ackland et al (2003) results. Anaerobic peak power and mean power it`s near to elite kayakers. In conclusion these kayaker have a good state in anthropometrical and physiological variables.